Antibacterial Activity Of Daemonorops Draco (Willd) Blume Fruit Ethanol Extract Against Some Bacterial Pathogens - Apriani, Aida; Masfria, Masfria; Sitorus, Panal (International Journal of Science, Technology & Management, 2022)
Daemonorops draco (Willd.) Blume fruit has been used as a traditional medicine which is well-known as an antiseptic, stimulates blood circulation, anti-microbial, anti-viral, anti-tumor, wound medicine, diarrhea, fractures, gonorrhea, minor burns and others. Daemonorops draco (Willd.) Blume belonging to the Arecaceae tribe contains a class of chemical compounds such as alkaloids, flavonoids, tannins, saponins, steroids/triterpenoids, and glycosides. Flavonoid compounds, saponins and tannins are chemical compounds that have potential as antibacterial and antiviral. This study aims to determine the characteristics of simplicia, phytochemical screening, antibacterial activity test of the ethanol extract of Daemonorops draco (Willd.) Blume fruit.Simplicia characterization includes organoleptic, macroscopic, microscopic examination, determination of water content. Extraction was carried out by maceration using ethanol as a solvent. Phytochemical screening was carried out on simplicia powder, fruit ethanol extract Daemonorops draco (Willd.) Blume, assay of antibacterial activity of extract using diffusion methodagar by observing the zone of inhibition against several test bacteria: Staphylococcus aureus, Escherichia coli, Salmonella thypi. The results of simplicia characterization obtained water content of 4.65%. The results of the phytochemical screening test of simplicia and ethanolic extracts contained groups of alkaloids, flavonoids, glycosides, saponins, tannins, steroids/triterpenoids. Having the highest antibacterial activity was ethanol extract from Gram positive Staphylococcus aureus bacteria followed by Gram negative bacteria Escherichia coli and Salmonella thypi at a concentration of 500 mg/ml with an effective inhibitory diameter of 15.5 mm, Escherichia coli at 14.3 mm, Salmonella typhi at 14, 8 mm.